Biogenic synthesis of iron oxide nanoparticles using Hibiscus sabdariffa extract: Potential for antibiotic development and antibacterial activity against multidrug-resistant bacteria - Wahran M. Saod; Mohammed Salih Al-Janaby; Estabraq W. Gayadh; Asmiet Ramizy; Layth L. Hamid (Current Research in Green and Sustainable Chemistry, 2024)
Expand emergence of antibiotic resistance in different strains of bacteria has become an essential global problem in the health area. This case leads to several medical difficulties such as increased death rates, high therapy costs and long-infected patients remaining in hospitals. This study is designed to evaluate the efficacy of incorporating antibiotics with nanomaterials to combat MDR bacteria. biogenic FeO NPs were synthesised using Hibiscus sabdariffa calyces extract through an eco-friendly and easy method. FeO NPs were subjected to characterisation using some physical techniques, including UV–Visible, FTIR, XRD, SEM and AFM. Characterisation results indicated that the FeO NPs exhibited a crystalline structure, mainly spherical, absorption peak between 290 and 300 nm, and had an average size of 61 nm. The bactericidal activity of the FeO NPs was estimated against three MDR pathogenic bacteria. The results revealed the efficacy of the FeO NPs in inhibiting the growth of the MDR K. pneumoniae, E. coli, and P. aeruginosa. The MIC of the FeO NPs against these bacteria was determined to be 6.25, 12.5, and 25 μg/ml for K. pneumoniae, E. coli, and P. aeruginosa, respectively. Moreover, when combined with antibiotics, the incorporation of FeO NPs significantly enhanced the effectiveness of multiple antibiotics against MDR bacteria. These findings suggest that FeO NPs have promising applications as antibacterial compounds and as additives to enhance antibiotic efficacy.